دور الملك عبدالعزيز في تأسيس المملكة العربية السعودية في اهتمامات صحيفة الشهاب 1932 - 1934 م. - تاونزة، محفوظ; سبيحي، عائشة (جامعة معسكر - مخبر البحوث الاجتماعية والتاريخية, 2019)
شهدت شبه الجزيرة العربية أحداثا وتطورات سياسية هامة خلال فترة (1934- 1932)، أبرزها تأسيس المملكة العربية السعودية على يد الملك عبد العزيز بن سعود. هذه الأحداث والتطورات كانت محل اهتمام صحيفة الشهاب وذلك بمواكبتها وتحليل خلفياتها، وإبراز مواقفها المؤيدة لجهود الملك السعودي في توحيد مختلف أجزاء المملكة العربية السعودية. كما لم تتوان الصحيفة في شجب الأطماع الاستعمارية الغربية في المنطقة وفضحها، والإشادة بتفطن الملك السعودي لها، ونصرته في إحباط ثورتي حامد بن رفادة 1932 وعسير 1933م، وفي حربه ضد اليمن 1934، باعتبارهم مؤامرات خارجية مدبرة من قبل القوى العربية الرجعية المعادية للملك وسياسته، وكذا القوى الغربية الاستعمارية وعلى رأسها بريطانيا وإيطاليا، وهللت بتكليل جهود الملك بالانتصار على خصومه وتمكنه من تثبيت دعائم ملكته.
The Arab peninsula has witnessed some events and crucial political evolutions during the period between (1932 and 1934), the most important one among them is the creation of the kingdom of Saudi Arabia by King Abdul-Aziz ben Saud. These events and political evolutions had been among the interests of Echihab magazine. This was done through accompanying them and analyzing their backgrounds as well as showing its positions by supporting the Saudi King’s efforts unifying the different parts of the kingdom of Saudi Arabia. The magazine Echihab has also condemned the western colonial ambitions in the region as well as its denunciation and praising the king’s discoveries to these ambitions and his victorious supports to give up the uprising of RIFADA in 1932, and the one of ASSIR, adding to his war against Yemen, he did so for the uprisings were but external conspiracies orchestrated by the retro-power anti king and his policies and the western colonial powers, on their head, Britain and Italy that cheered the efforts of the king for his victory over his opponents and his capacity to consolidate his kingdom.
Keywords: التطورات السياسية -- الصحف العربية -- الثورات السعودية -- النخب الجزائرية -- الوطن العربي